2014
DOI: 10.3390/w6123888
|View full text |Cite
|
Sign up to set email alerts
|

Application of Displacement Height and Surface Roughness Length to Determination Boundary Layer Development Length over Stepped Spillway

Abstract: Abstract:One of the most uncertain parameters in stepped spillway design is the length (from the crest) of boundary layer development. The normal velocity profiles responding to the steps as bed roughness are investigated in the developing non-aerated flow region. A detailed analysis of the logarithmic vertical velocity profiles on stepped spillways is conducted through experimental data to verify the computational code and numerical experiments to expand the data available. To determine development length, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 60 publications
0
5
0
1
Order By: Relevance
“…It was suggested that the energy dissipation rate in the different types of pooled weirs followed the order, two-sided and central pool, full pool and central pool, full pool and two-sided pools, and full pool. Cheng et al [40] measured the logarithmic velocity profile in a stepped spillway using numerical simulation and compared it with experiments. According to their researches, the air inception location over stepped spillways exits until the boundary layer thickness is between the range of 0.72 and 0.79.…”
Section: LImentioning
confidence: 99%
“…It was suggested that the energy dissipation rate in the different types of pooled weirs followed the order, two-sided and central pool, full pool and central pool, full pool and two-sided pools, and full pool. Cheng et al [40] measured the logarithmic velocity profile in a stepped spillway using numerical simulation and compared it with experiments. According to their researches, the air inception location over stepped spillways exits until the boundary layer thickness is between the range of 0.72 and 0.79.…”
Section: LImentioning
confidence: 99%
“…Para a verificação do simulador numérico desenvolvido, na versão bidimensional, a geometria do problema foi a mesma que a descrita em Chanson e Toombes (2002) e Cheng et al (2014) (Fig. 3).…”
Section: Vertedouro Bidimensionalunclassified
“…In addition to these experimental studies, flow on stepped spillways have been modeled numerically with a high degree of accuracy using computational fluid dynamics (CFD). In numerical studies of stepped spillways, the flow over the stepped spillway is investigated by the volume of fluid (VOF) method, with turbulence closures of the k-ε family [26][27][28][29][30][31][32][33][34][35]. For instance, Wan et al [36] have used VOF and the realizable k-ε model to determine the inception point of air entrainment in various stepped spillways, including flat steps, pooled steps, and round steps.…”
Section: Introductionmentioning
confidence: 99%